The Barriers to Interprofessional Collaborative Practice: Perspectives from Australian Physiotherapy Private Practitioners - Seaton, Jack; Jones, Anne; Johnston, Catherine; Francis, Karen (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2023)
Background: Despite the growing presence of physiotherapy private practitioners within Australia’s healthcare workforce, little is known about their perspectives of interprofessional collaborative practice (IPCP). This study aims to explore the barriers to IPCP from the perspective of Australian physiotherapy private practitioners.Methods: Semi-structured interviews were conducted with 28 physiotherapists and 64 hours of observation was completed in 10 private practice sites in Queensland, Australia. Interview and observation data were pooled and analyzed using reflexive thematic analysis.Findings: Data analysis produced five themes that characterized physiotherapists’ perspectives of IPCP: a) competition for clientele, b) personal attitudes and beliefs, c) time constraints and work schedules, d) geographic location, and e) rules of funding schemes.Conclusion: The findings from this study suggest that implementing IPCP in the Australian physiotherapy private practice setting presents several challenges. Financial concerns, such as physiotherapy private practitioners’ perceived need to compete for clientele, were significant barriers to IPCP. The introduction of financial incentives and adoption of alternative payment models may be necessary to provide physiotherapy private practitioners with a clear motivation to engage in IPCP. The need for more formal opportunities to bring health practitioners from diverse professional backgrounds together to gain new insights and knowledge of other professions’ expertise and challenge their own assumptions was also highlighted.